PENGEMBANGAN PERANGKAT PEMBELAJARAN PADA MATERI BANGUN RUANG SISI DATAR BERBASIS MODEL PROJECT BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA - Yayan Sofyan; Sumarni Sumarni; Mohamad Riyadi (SIGMA: JURNAL PENDIDIKAN MATEMATIKA, 2021)
This study aims to describe the procedure for developing flat-sided geometry learning tools with the Project Based Learning model to improve students' mathematical problem solving abilities and to find out the validity of flat-sided geometry learning devices with Project Based Learning models to improve students' mathematical problem solving abilities. The tools developed in this research are Student Project Worksheets and evaluation tools using a project based learning model. The research on the development of this learning device uses the Research and Development (RnD) type of research. To produce these learning tools, development research refers to the Plomp development model which consists of three phases, namely the Preliminary Phase, the Development or Prototyping Phase, and the Assessment Phase. development research produces learning tools for flat-sided shapes with a project based learning model to improve students' mathematical problem solving abilities and produce valid learning tools with the results of validating learning tools in the form of LKPS getting an average result of 4,33 including in the very valid category and for learning tools in the form of an evaluation tool got an average result of 4.24 included in the very valid category